Nutritional Knowledge and Perceived Stress in National Male Boxers - Acar, Hakan (Progress in Nutrition, 2022)
National athletes should have a good nutrition for sustainable sports performance or development; and perceived stress can affect nutrition. The aim of this study is to determine nutritional knowledge and perceived stress in national male boxers. This cross-sectional study was conducted 20 national male boxers in June 2020. Participants completed sociodemographic form, and Nutritional Knowledge Level and Perceived Stress Scale (PSS) questionnaires that included questions related to their stress, eating habits, nutritional knowledge etc. Body weight and height of participants were measured. Descriptive statistics and Pearson correlation analysis were used to evaluate the data obtained. In the present study, 20 male boxers were participated, the mean age was 23.35±2.99 years. Their mean BMI and sports age was 23.03.49±3.87 kg/m2 and 11.7±3.7 years. All athletes were training 6 days a week for a total of 16 hours. Participants were generally eating regularly and had a good nutritional knowledge. There was a significant correlation between age and sports age (p=0.027).In conclusion, it can be said that national male boxers nutritional knowledge were at a good level. It is recommended that nutritional knowledge and stress assessment tools should be used to determine the factors preventing good performance, it should be intervened where necessary.